PENGARUH LATIHAN DOUBLE LEG HOP PROGRESION TERHADAP POWER OTOT TUNGKAI PADA TIM SEPAK TAKRAW SMA NEGERI 1 PUJUD KABUPATEN ROKAN HILIR - Iis Wadi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: The problem in this research is that athletes are not maximal in jumps when blocking and hitting (nails). The title being investigated in this research is "The effect of double leg hop training on leg muscle strength in the soccer team at SMA Negeri 1 Pujud Rokan Hilir Regency". The purpose of this research was to determine whether there was an increase in leg muscle strength. The form of this study utilized a one-group pretest-post-test design approach with a population of Sepak Takraw athletes at SMA Negeri 1 Pujud. The data in this study was the full population of 8 subjects. The instrument used in this research was a vertical force jump test that aims to determine how much force the athlete has. Based on statistical data analysis, it was obtained that the mean variable X was 23.43 and the mean variable Y 23.58 for the t-distribution test of the effect between the variable x and the variable y got the value of t = 8.235, then t count> t-table, namely (8,235)> (1,895), then Ha is accepted, in other words, there is an effect of double leg hop progression training on leg muscle strength in the takraw team of SMA Negeri 1 Pujud Rokan Hilir.Key Words: Exercise Double Leg Progression, Leg Muscle Strength